Pembelajaran Terdeferensiasi Berbasis Lingkungan Sekitar pada Materi Pesawat Sederhana di Sekolah Menengah Pertama - Arif Kristanta (Jurnal Didaktika Pendidikan Dasar, 2024)
Online learning during the COVID-19 pandemic which lasted for almost two years had an impact on reducing student motivation and learning outcomes. This research aims to determine the extent to which the motivation and learning outcomes of class VIIIA students at SMPN 2 Tanjungsari have increased in the 2022/2023 academic year in environmentally based differentiated learning about simple airplanes. The method used is the Classroom Action Research (PTK) Kemmis and Targart model with two cycles where one cycle consists of four activities, namely planning - action and observation - reflection. One cycle consists of two face-to-face meetings. The instrument to determine the increase in learning motivation is in the form of an observation sheet on students' activeness in participating in learning and students' seriousness in carrying out assignments. Instruments to determine improvements in learning outcomes are student worksheets and summative tests. The results of this research are an increase in students' learning motivation which is marked by an increase in the number of groups of students working on and collecting assignments by 30% from 50% before learning to 87.5% during learning and an increase in learning outcomes as indicated by an increase in the average test score. summative as much as 16.59% from 44.6 before learning to 52 after learning. The number of students who scored above the KKM increased from 1 student before learning to 7 students after learning.